Bone mineral density screening and its accordance with Canadian clinical practice guidelines from 2000–2013: an unchanging landscape in Saskatchewan, Canada. Issue 1 (December 2015) - McLeod, Katherine; Johnson, Shanthi; Charturvedi, Rahul; Onge, Jennifer; Lionel, Amrita; Verma, Ashok
Abstract Summary We examined the clinical characteristics of patients who underwent initial dual energy X-ray absorptiometry (DXA) testing at a primary care facility from 2000 to 2013, and whether these factors changed over time in accordance with Canadian clinical practice guidelines. The burden of osteoporosis remains high and largely unchanged and clinical practice guidelines are not being followed, overall. Purpose This study examined the clinical risk factors, therapeutic health behaviors, and bone mineral density (BMD) status of patients who underwent initial DXA testing at a primary care facility in Saskatchewan, Canada, and whether these factors changed over time from 2000 to 2013 in accordance with Canadian clinical practice guidelines. Methods We conducted a retrospective cross-sectional medical chart audit of 800 patients 50 years of age and older who underwent their first DXA test to assess BMD status. Data was extracted from 2000 to 2013 and further stratified into four periods (2000–2001, 2002–2006, 2007–2009, and 2010–2013;n  = 200 each period) based on the years when practice guidelines were implemented. Extracted data included BMD outcomes, clinical risk factor indicators for DXA testing, and recommendations for therapeutic health behaviors outlined in the clinical practice guidelines. Results There were no differences in BMD status across the four time stratas (p  = 0.430). Overall, most clinical risk factors had little change over time. The number of males screened significantly increased over time (p  < 0.05), and osteoporosis drug therapy use decreased from 2000–2001 to 2010–2013 (p  < 0.001). Increasing age, body mass <60 kg, and history of adult fracture were significant independent predictors of osteoporosis diagnosis. Conclusions The burden of osteoporosis remains high and largely unchanged in Saskatchewan, Canada. These results serve to inform strategies to enhance health-care provider awareness and compliance with practice guidelines, as well as improve screening rates and patient health behaviors.